Perkembangan Teknologi E-Business Terhadap Globalisasi Modern Pada Saat Ini - Embun Febryanti Panggabean; Hesty Ananta Yunas; Taufiqurrahman Taufiqurrahman; Nurbaiti Nurbaiti (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
Current technological advances reflect significant changes from the previous technological era to the present. Especially, internet development has become a trend among local and international communities. For example, e-business is in the spotlight because it makes things easier and gives business entities a lighter burden, especially for those who have the ambition to achieve success. E-business not only increases marketing networks, but also increases employee productivity within the company. Information technology provides the ability to initiate business creativity and innovation quickly and efficiently. It is important for businesses to see new opportunities amidst continued development, with the key to success returning to motivation and innovation, thereby creating technology that is always up to date.